Unstable exchange rates and trade policy: An impetus for reforming GATT? - Hans Mayrzedt (Intereconomics, 1979)
Floating exchange rates affect two basic principles of GATT, namely: stability of trade policy conditions and reciprocity of trade concessions. What is the relevance of the changes to foreign trade? What possibilities for surmounting the new problems exist in the realm of external economic relations?
Keywords: 330; GATT